Applications of the Insieme Platform: A Case Study - Kocuvan, Primož; Dovgan, Erik; Ražman, Simon; Palčič, Devid; Gams, Matjaž (Informatica, 2022)
The information society has significantly changed the field of medicine. Several decades ago when a person got sick, a doctor examined a patient and prescribed some medicine with a patient more or less unaware of the true nature of the problem. Even if explained, many patients did not understand much due to the lack of medical knowledge. Today, knowledge is widely accessible through the web and many patients try to self-diagnose or at least get another opinion using popular search engines and specialized web applications. However, many of them provide misinformation due to the lack of proper education of the provider or the lack of understanding of the user. To overcome these issues, we developed a verified medical platform (Insieme platform) that includes medical data, applications and services. This article provides a list of applications in the Insieme platform, their descriptions and how to use them.